2017
DOI: 10.1136/jmedgenet-2017-104626
|View full text |Cite
|
Sign up to set email alerts
|

Genetic causes of optic nerve hypoplasia

Abstract: Optic nerve hypoplasia (ONH) is the most common congenital optic nerve anomaly and a leading cause of blindness in the USA. Although most cases of ONH occur as isolated cases within their respective families, the advancement in molecular diagnostic technology has made us realise that a substantial fraction of cases has identifiable genetic causes, typically de novo mutations. An increasing number of genes has been reported, mutations of which can cause ONH. Many of the genes involved serve as transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 93 publications
1
24
0
Order By: Relevance
“…In patients with optic nerve hypoplasia (ONH), neuroimaging also shows abnormalities in ventricles or whiteor gray-matter development, septooptic dysplasia, hydrocephalus, and corpus callosum abnormalities. [23][24][25] This last feature was also documented in our patient in addition to a posterior lobe of the pituitary gland ectopia. Indeed, it has been described that incidence of neurologic abnormalities is greater in patients with bilateral optic nerve hypoplasia (65%) than patients with unilateral ONH.…”
Section: Discussionsupporting
confidence: 81%
“…In patients with optic nerve hypoplasia (ONH), neuroimaging also shows abnormalities in ventricles or whiteor gray-matter development, septooptic dysplasia, hydrocephalus, and corpus callosum abnormalities. [23][24][25] This last feature was also documented in our patient in addition to a posterior lobe of the pituitary gland ectopia. Indeed, it has been described that incidence of neurologic abnormalities is greater in patients with bilateral optic nerve hypoplasia (65%) than patients with unilateral ONH.…”
Section: Discussionsupporting
confidence: 81%
“…Parr et al reviewed clinical records for 83 children, identifying a group of children with optic nerve hypoplasia or septo‐optic dysplasia, and found that 31 per cent also had a clinical diagnosis of autism. This is supported by Chen et al who note that advances in genotyping will reveal that a number of apparently idiopathic cases of optic nerve hypoplasia likely have underlying genetic causes.…”
Section: Retina Function and Structurementioning
confidence: 84%
“…It is reasonable to assume that genetic mutations in these parts may contribute to the broad phenotype and reduced penetrance, and this should be further studied. Chen et al have published an excellent review of genetic causes of ONH which highlighted 16 genes [12]. To this list we suggest to add COL4A1 and COL4A2, which seem to be important genetic contributors to ONH.…”
Section: Discussionmentioning
confidence: 99%
“…Although most cases of ONH are sporadic, there are also familial cases suggesting a genetic aetiology [9,10]. HESX1 was the first gene to be associated with ONH [10], but only few cases have been reported [11,12]. Due to the increasing rate of genetic testing of affected individuals, several developmental genes have been proposed as candidate genes for ONH [12,13].…”
Section: Introductionmentioning
confidence: 99%